The Islamic Subject of Home Cinema of Kerala. (June 2019) - Karinkurayil, Mohamed Shafeeq
Migration to the Arabian Gulf as the experience of the state of Kerala has mostly been elided in mainstream Malayalam cinema. The digital revolution towards the end of the last century has spurred a local film practice in northern Kerala, usually called 'Home Cinema'/'home video'/'home film' and so on. Home Cinema of Kerala is locally produced low-quality CD/DVD video productions which are full-length feature films distributed through video shops, stationeries, bookstores and so on. Home Cinema, synonymous in its beginning with the films of Salam Kodiyathur, began as an attempt to oppose what was perceived as the immoral qualities of mainstream cinema, both global and regional. As a counter to the mainstream, Kodiyathur attempted to formulate Islamic cinema but in the idiom of a strand of mainstream Malayalam cinema. This article looks at the constitution of the Islamic subjects of these cinemas as negotiating the figure of the migrant Muslim in the dominant idiom of Malayalam cinema.